The relationship between firms that start operating as unregistered and firms' innovation: The moderating effect of access to finance - Sam Njinyah; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The purpose of this paper is to examine the relationship between a firm starting operation informally and its future innovation and whether this relation is moderated by institutional support (having access to finance from financial institutions to run their business). Data from the World Bank Enterprise Survey on 30 Eastern European and South-East Asian countries were analysed using probit regression analysis. The findings show that there is a positive significant relationship between firms that start operations informally and the firms' innovation and that such effect persists over time. We found that this relationship is stronger if the firms can gain access to finance to expand their business activities. Finally, our result shows that such a relationship is based on the type of innovation being pursued by the firm. By examining the moderation effect of access to finance on starting a business informally, we provide an alternative explanation to policymakers on how to deal with informal firms to benefit from their contribution to growth.
Keywords: 330; Informality/unregistered firms; Innovation; Institutions; Eastern European and South East Asia